Cultivating Global Citizens: Cultural Awareness, Critical Thinking, and Intercultural Competence in High School Education - Djono, Djono; Purwanta, Hieronymus; Pelu, Musa; Herimanto, Herimanto; Sutiyah, Sutiyah; Ashari, Hasan (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to analyze the level of local cultural awareness of high school students in Karanganyar Regency and explore its relationship with critical thinking skills and intercultural competence. This study employed a quantitative approach with a survey design, collecting data through a 3-point Likert scale-based questionnaire consisting of factual and valence statement items, as well as additional indicators to measure critical thinking and intercultural competence. The research sample consisted of 110 high school students in Karanganyar Regency, selected purposively. The data were analyzed using descriptive quantitative techniques through percentage categorization and comparison of scores across variables. The results showed that 90% of students were in the medium cultural awareness category, 2.7% in the high category, and 7.3% in the low category. Notably, one student from the high category scored 98.1% for cultural awareness and achieved perfect scores for critical thinking and intercultural competence, while students from the low category only achieved 57.4% in cultural awareness, with critical thinking scores of 61.9% and intercultural competence scores of 72.2%. These findings suggest a tendency that students with high levels of cultural awareness also show better mastery of critical thinking and intercultural skills.